2017
DOI: 10.1111/jzo.12471
|View full text |Cite
|
Sign up to set email alerts
|

Wild boar under fire: the effect of spatial behaviour, habitat use and social class on hunting mortality

Abstract: The wild boar (Sus scrofa) is an ungulate of major management concern, often controlled only by indiscriminate, recreational hunting, which represents its main cause of death. Several studies have dealt with the effects of hunting on wild boar populations, pointing out controversial changes in spatial behavior and habitat use related to it. However, little information on the relationship between spatial behavior, habitat use and hunting mortality is available. In this study, 105 wild boars were monitored by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…It has been shown that the proportion of forests in the home range, landscape complexity and habitat diversity, can play a major role in predicting hunting mortality (Merli et al ., ). In this regard, it is noteworthy that all 16 individuals tracked in this study survived the 2006–2007 hunting season.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the proportion of forests in the home range, landscape complexity and habitat diversity, can play a major role in predicting hunting mortality (Merli et al ., ). In this regard, it is noteworthy that all 16 individuals tracked in this study survived the 2006–2007 hunting season.…”
Section: Discussionmentioning
confidence: 97%
“…where Hp = estimated host population size, Hb = number of animals hunted in a given year, and P hunt = estimated proportion of the population hunted annually, based on published data for wild boar [43][44][45][46], and deer [47][48][49]. The proportion of infected individuals by species and the ratio of TB-infected non-bovine hosts to cattle were estimated in a Bayesian framework from the posterior distribution of the number of infected animals.…”
Section: Methodsmentioning
confidence: 99%
“…Wildlife population abundance was modeled as expert opinion Equation (2), when published estimates were available; or else based on official data on the number of animals hunted, corrected by the estimated proportion of the population hunted: where Hp = estimated host population size, Hb = number of animals hunted in a given year, and P hunt = estimated proportion of the population hunted annually, based on published data for wild boar [ 43 , 44 , 45 , 46 ], and deer [ 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the causes of mortality, 85% of the dead animals were shot, 3% died from disease or starvation, and 3% were killed in traffic accidents (Keuling et al., ). Mortality due to hunting is slightly biased towards adult males (Keuling et al., ; Merli et al., ). In a recent study in central Italy, 97% of the mortality was due to hunting or poaching, and the annual mortality rate was about 50% (re‐calculated).…”
Section: Assessmentmentioning
confidence: 99%
“…In a recent study in central Italy, 97% of the mortality was due to hunting or poaching, and the annual mortality rate was about 50% (re‐calculated). Wild boar with more forest in their home range was less likely to be culled (Merli et al., ). Hence, wild boar mortality in central Europe is relatively low and mostly due to hunting.…”
Section: Assessmentmentioning
confidence: 99%